EFFICACY OF IMAZETHAPYR AND QUIZALOFOP-ETHYL HERBICIDES ON GROWTH AND YIELD OF CHICKPEA - V. V. GOUD; N. B. MURADE; M. S. KHAKRE; A. N. PATIL (The Bioscan, 2013)
A field experiment was conducted during rabi 2009-10- and 2010-11 to study the response of post–emergence herbicides on growth and yield of chickpea grown in clayey soil. Among herbicides highest yield and yield attributes, viz. branches/plant, pods/plant, seed weight/plant and 100-seed weight were recorded with application of imazethapyr and quizalofop-ethyl @ 75 g/ha at 25 and 35 DAS, respectively, over weedy check. However, application of higher dose of imazethapyr @ 100 g/ha at 25 and 35 DAS significantly reduced the plant height (54.28), branches/plant (21.61), pods/plant (48), seed weight/plant (16.3) and root nodules (8.5) over lower dose of herbicides (50 g/ha), on the contrary 100-seed weight (38.946) increased over application of reduced doses. The post-emergence application of imazethapyr and quizalofop-ethyl @ 50 g/ha at 25 and 35 DAS was inefficient in effective control of weeds but at higher rate of application 75 and 100 g/ha was effective but phytotoxic on chickpea. Among the herbicides imazethapyr and quizalofop-ethyl at each dose rates decreased the grain yield, however, the intensity was more at higher rate of application i.e. 100 g/ha. It has been observed that imazethapyr and quizalofop-ethyl were injurious to the chickpea and injury increased with increase in the concentration of both these herbicides. Toxicity was more with imazethapyr as compared to quizalofop-ethyl at all rates of application. Chickpea injury was minimal at 35 days after application at all rates, which was insignificant with lower dose of 50 g/ha, however, which was inefficient for effective weed control. The results implied that a higher concentration of imazethapyr resulted in a decline in growth, yield attributes and yield of chickpea. There is need to change in herbicide selection or application method in order to have better weed control